(untitled) - Swan, Michael (Cambridge, 1999)
The New Cambridge English Course is a course teachers and students can rely on to cover the complete range and depth of language and skills needed from beginner to upper-intermediate level. Each level is designed to provide at least 72 hours of class work using the Student's Book, with additional self-study material provided in the Practice Book. The course has a proven multi-syllabus approach which integrates work on all the vital aspects of language study: grammar, vocabulary, pronunciation, skills, notions and functions.
Keywords: English language,Listening; Study and teaching